PENGARUH KARAKTERISTIK PEMERINTAH DAERAH TERHADAP EFISIENSI KINERJA KEUANGAN PEMERINTAH DAERAH - Kusuma, Aulia Rizka; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to test the influence of the characteristic of the local government which is proxy by thesize of local government, prosperity, the dependence level on central government, leverage, and local expenditureto the financial performance of the local government based on the performance efficiency ratio. The population isall cities/districts local government in East Java Province in 2013-2015 periods. The sample collection techniquehas been carried out by using purposive sampling method and based on the predetermined criteria so 35cities/districts have been selected as samples. The secondary data has been carried out by using LKPD from theAudit Board of the Republic of Indonesia (BPK) East Java Province Representative. The analysis technique hasbeen carried out by using multiple linear regressions analysis. The data examination has been carried out byusing SPSS software 23.0 version. The result of R2 test shows that the independent variable is 35,5% and is64,5% has been influenced by other variables which are not included in the research. The result of t test showsthat prosperity and local expenditure has positive influence to the financial performance of local governmentbased on the performance efficiency ratio whereas the size of local government size, the dependence level oncentral government, and leverage do not have any influence to the financial performance of local governmentbased on the performance efficiency ratio.Keywords: The characteristics of local government, financial performance of local government, performanceefficiency.